Morphological features of liver effect in patients with chronic hepatitis B with HIV-coinfection - S. Ch. Soni; L. V. Moroz; A. O. Havrylyuk; K. D. Chichirelo-Konstantynovych (Kazimierz Wielki University, 2019)
The article presents modern views on morphological disturbances in liver tissue at HBV/HIV patients. It was shown that "matte-glass-like" hepatocytes, inflammatory cell lymphocytic infiltrate of varying degrees and liver fibrosis are specific signs of HBV/HIV patients. Specific morphological signs of liver damage in co-infected patients confirm that HIV-infection worsens histological structure as well as functional balance. Therefore, development of pathohistology method of diagnostics becomes more and more necessary in patients with complicated liver injuries. New findings can give opportunity for early screening HBV-infected patients for HIV-markers, prescribing antiviral treatment at early stages. The research will build new approach for avoiding fast fibrogenesis.